Soil Flora in Soil Physical Condition Improvement and their impact on plant growth - Goswami, Rakesh Giri; Singh, Ashish Kumar (Indian Farming, 2017)
Plant roots create voids and microspores in the soil so that air and water can move through the soil. Plant roots supply food for microorganisms (especially fungus) and burrowing soil fauna that also keep the soil from compaction. Organic residues left behind by the decaying plants are lighter and less dense than clay, silt, and sand particles which ultimately decrease the average soil density. Soil microflora improves plant growth. Soil fauna improve aeration, porosity, infiltration, aggregate stability, litter mixing, improved N and C stabilization, C turnover and carbonate reduction and N mineralization, nutrient availability and metal mobility. Thus, soil physical condition can be improved through proper management of soil organism through addition of organic manures which ultimately enhance the growth of plants.